Benefits of exercise training on pulmonary arterial pressure as measured by echocardiography in patients with pulmonary hypertension - Firdaus, Muhammad; Martini, Heny (Universitas Brawijaya, 2025)
Pulmonary hypertension (PH) is a substantial worldwide health concern that impacts around 1% of the population, in especially among the elderly. PH is defined by a mean pulmonary arterial pressure (mPAP) over 20 mmHg and is linked to significant morbidity and mortality. Optimal care depends on precise evaluation of mPAP, which acts as a crucial diagnostic and prognostic marker. Recent research emphasizes the significance of exercise training as a secure and economical intervention that can result in significant enhancements in hemodynamic parameters, such as decreased mPAP and increased cardiac output. Engaging in exercise training stimulates the expansion of blood vessels in the lungs, enhances the functioning of the right ventricle, and reduces persistent inflammation, therefore enhancing the overall ability to exercise and the quality of life for those with pulmonary hypertension. Echocardiography is crucial for monitoring mean pulmonary arterial pressure and evaluating right ventricular function. mPAP is a critical parameter in the evaluation and diagnostic testing for pulmonary hypertension (PH) due to its strong correlation with disease severity and prognosis. Exercise training confers a multitude of advantages to both the cardiovascular system and skeletal muscle systems. Exercise training is generally considered safe, yet, it is important to provide thorough supervision to reduce the occurrence of negative outcomes, especially in patients with advanced illness. In summary, including exercise training into the treatment plan for patients with pulmonary hypertension shows encouraging advantages, justifying more investigation and standardization of exercise procedures to enhance patient results.